(untitled) (Research, Society and Development, 2020)
The aim of this study was to identify the epidemiological profile and pattern of lethal injuries in female victims of homicide presenting injuries in the craniofacial region as a cause of death, from January to December 2018. This was a cross-sectional, retrospective, descriptive study carried out through the evaluation of tanatological reports in an forensic medicine institute. Given the inclusion criteria of study, the sample was 62 cases, with predominance of women aged 19 to 29 years (46.9%), brown /black (76.9%) on weekdays and held on public roads. The most prevalent lesions were made using the blunt-force instrument (83.4%), transfixing (43.8%), with skull fractures (81.2%) and 8.2%. on the face. The results showed that the female gender reflects a sociodemographic profile similar to that of the global homicide victims in the country and the pattern of lesions that cause the death of women in the craniofacial is composed of lesions performed by a high-energy instrument that produces important damage and fractures to the structures of the region.